Coccolith volume of the Southern Ocean coccolithophore Emiliania huxleyi as a possible indicator for palaeo-cell volume - Muller, MN; Brandini, FP; Trull, TW; Hallegraeff, GM (Geobiology, 2021)
Coccolithophores are a key functional phytoplankton group and produce minute calcite plates (coccoliths) in the sunlit layer of the pelagic ocean. Coccoliths significantly contribute to the sediment record since the Triassic and their geometry have been subject to palaeoceanographic and biological studies to retrieve information on past environmental conditions. Here, we present a comprehensive analysis of coccolith, coccosphere and cell volume data of the Southern Ocean Emiliania huxleyi ecotype A, subject to gradients of temperature, irradiance, carbonate chemistry and macronutrient limitation. All tested environmental drivers significantly affect coccosphere, coccolith and cell volume with driver‐specific sensitivities. However, a highly significant correlation emerged between cell and coccolith volume with V coccolith =0.0120.001* V cell +0.2340.066 (n=23, r 2 =.85, p <.0001, σ est =0.127), indicating a primary control of coccolith volume by physiological modulated changes in cell volume. We discuss the possible application of fossil coccolith volume as an indicator for cell volume/size and growth rate and, additionally, illustrate that macronutrient limitation of phosphorus and nitrogen has the predominant influence on coccolith volume in respect to other environmental drivers. Our results provide a solid basis for the application of coccolith volume and geometry as a palaeo‐proxy and shed light on the underlying physiological reasons, offering a valuable tool to investigate the fossil record of the coccolithophore E. huxleyi .